Witness 8 - Cavanagh, Steve (Cavanagh, Steve. Eddie Flynn novel, 2025)
"Something is wrong with Ruby Johnson. A former resident of the ultra-elite Manhattan upper class, Ruby now works as a maid in the type of houses she used to live in. Unassuming, she sees everyone's dirty secrets from the inside of their beautiful, renovated brownstones. But when Ruby witnesses a murder, she has wicked plans in mind that don't involve telling the authorities the truth. Eddie Flynn, streetwise ex con-artist-turned-defense attorney, is the only lawyer in New York City willing to take on hopeless cases. And none is more hopeless than John Jackson's--the gun that killed his neighbor found, with Jackson's DNA, in his own home. Flynn and his unconventional team will need to use every trick they know to keep an innocent man from being locked up. But to save his client's life, Eddie must first protect his own, as the scariest organized criminals in the city are out for his head"--